Factors influencing teacher career satisfaction, teacher collaboration and everyday challenges : An exploratory factor analysis - Narayan, Nilesh Anish (Malaysian online journal of educational sciences, 2016)
The main purpose of this study is to assess the construct validity of Australian eighth grade mathematics teachers' perceptions towards their career satisfaction, their teaching practice and the everyday challenges encountered in schools. The data were utilised from the Trends in International Mathematics and Science Study where a total of 802 eighth grade mathematics teachers participated. Exploratory factor analysis with statistical tests were utilised to analyse the data. Three factors career satisfaction, teacher collaboration and everyday challenges were derived from exploratory factor analysis. The factors had a reliability coefficient of: career satisfaction (0.802), teacher collaboration (0.838) and everyday challenges (0.777). The findings suggested that female teachers had a higher career satisfaction level and highly experienced teachers encountered more everyday challenges. This study could be helpful to enhance the level of career satisfaction for teachers and assist in reduction of everyday challenges. Future research could investigate actual reasons for lower satisfaction level for the teachers [Author abstract]